A Comprehensive Database of Expert‐Curated Occurrences for the Genus Carex L. (Cyperaceae) - María Sanz‐Arnal; Pablo García‐Moro; Carmen Benítez‐Benítez; Marina Coca‐de‐la‐Iglesia; Angélica Gallego‐Narbón; Consolación Barciela; Fabrizio Bartolucci; Prabin Bhandari; Matthew Bradley; Asunción Cano; Antoine Derouaux; Sabina Donadío; et al. (Global Ecology and Biogeography, 2025)
Motivation Geographic occurrences are essential for biodiversity studies, but publicly available repositories like GBIF often contain errors and biases, especially for taxonomically complex groups like Carex L. (Cyperaceae). This work provides an expert‐curated global dataset of occurrences compiled from different sources to enhance data accuracy and usability. The final dataset includes 384,067 occurrences of 1790 Carex species. Main Types of Variables Contained The dataset includes species occurrence records with geographic coordinates, taxonomic identifications, and curation flags (e.g., introduced, erroneous records). Spatial Location and Grain The dataset covers a global scale, using the WGS84 projection. Spatial resolution is standardised to a minimum of three decimal degrees (~1 km, if possible). Time Period and Grain Online records span from 1950 to 2020, but some manually georeferenced records are earlier (1850). There is also fieldwork data after 2020, specifically up to 2023. Major Taxa and Level of Measurement Cyperaceae: Carex . Most records have species‐level identification, and some of them are identified at subspecies or variety levels. Software Format Data are supplied as comma‐separated values files with UTF‐8 encoding.

Corrigendum: Ten lessons on the resilience of the EU common fisheries policy towards climate change and fuel efficiency - A call for adaptive, flexible and well-informed fisheries management - Francois Bastardie; David A. Feary; Thomas Brunel; Laurence T. Kell; Ralf Döring; Sebastien Metz; Ole R. Eigaard; Oihane C. Basurko; Valerio Bartolino; Jacob Bentley; Benoit Berges; Sieme Bossier; et al. (Frontiers in Marine Science, 2023)

Ten lessons on the resilience of the EU common fisheries policy towards climate change and fuel efficiency - A call for adaptive, flexible and well-informed fisheries management - Francois Bastardie; David A. Feary; Thomas Brunel; Laurence T. Kell; Ralf Döring; Sebastien Metz; Ole R. Eigaard; Oihane C. Basurko; Valerio Bartolino; Jacob Bentley; Benoit Berges; Sieme Bossier; et al. (Frontiers in Marine Science, 2022)
To effectively future-proof the management of the European Union fishing fleets we have explored a suite of case studies encompassing the northeast and tropical Atlantic, the Mediterranean, Baltic and Black Seas. This study shows that European Union (EU) fisheries are likely resilient to climate-driven short-term stresses, but may be negatively impacted by long-term trends in climate change. However, fisheries’ long-term stock resilience can be improved (and therefore be more resilient to increasing changes in climate) by adopting robust and adaptive fisheries management, provided such measures are based on sound scientific advice which includes uncertainty. Such management requires regular updates of biological reference points. Such updates will delineate safe biological limits for exploitation, providing both high long-term yields with reduced risk of stock collapse when affected by short-term stresses, and enhanced compliance with advice to avoid higher than intended fishing mortality. However, high resilience of the exploited ecosystem does not necessarily lead to the resilience of the economy of EU fisheries from suffering shocks associated with reduced yields, neither to a reduced carbon footprint if fuel use increases from lower stock abundances. Fuel consumption is impacted by stock development, but also by changes in vessel and gear technologies, as well as fishing techniques. In this respect, energy-efficient fishing technologies already exist within the EU, though implementing them would require improving the uptake of innovations and demonstrating to stakeholders the potential for both reduced fuel costs and increased catch rates. A transition towards reducing fuel consumption and costs would need to be supported by the setup of EU regulatory instruments. Overall, to effectively manage EU fisheries within a changing climate, flexible, adaptive, well-informed and well-enforced management is needed, with incentives provided for innovations and ocean literacy to cope with the changing conditions, while also reducing the dependency of the capture fishing industry on fossil fuels. To support such management, we provide 10 lessons to characterize ‘win-win’ fishing strategies for the European Union, which develop leverages in which fishing effort deployed corresponds to Maximum Sustainable Yield targets and Common Fisheries Policy minimal effects objectives. In these strategies, higher catch is obtained in the long run, less fuel is spent to attain the catch, and the fisheries have a higher resistance and resilience to shock and long-term factors to face climate-induced stresses.

Moderation of buprenorphine therapy for cocaine dependence efficacy by variation of the Prodynorphin gene - David A. Nielsen; Robrina Walker; David P. Graham; Ellen M. Nielsen; Sara C. Hamon; Maureen Hillhouse; Dikla Shmueli-Blumberg; William B. Lawson; Kathy Shores-Wilson; Beverlyn D. Settles-Reaves; John Rotrosen; Madhukar H. Trivedi; et al. (European Journal of Clinical Pharmacology, 2022)

Ethnic diversity of DNA methylation in the OPRM1 promoter region in lymphocytes of heroin addicts - David A. Nielsen; Sara Hamon; Vadim Yuferov; Colin Jackson; Ann Ho; Jurg Ott; Mary Jeanne Kreek (Human Genetics, 2010)

A new approach to DNA bending by polyamines and its implication in DNA condensation - David Pastré; Olivier Piétrement; Fabrice Landousy; Loïc Hamon; Isabelle Sorel; Marie-Odile David; Etienne Delain; Alain Zozime; Eric Le Cam (European Biophysics Journal, 2006)

Studying the effect of a charged surface on the interaction of bleomycin with DNA using an atomic force microscope - Olivier Piétrement; David Pastré; Fabrice Landousy; Marie-Odile David; Stéphane Fusil; Loïc Hamon; Alain Zozime; Eric Le Cam (European Biophysics Journal, 2005)